الدوریات العلمیة المتخصصة فى مجال المکتبات والمعلومات بقواعد البیانات العربیة : دار المنظومة نموذجا - د. مها محمد ناجى (المجلة الدولية لعلوم المكتبات والمعلومات)
This paper studies thirty-three Arabic scholarly journals in the fieldof library and information science available at Dar Almandumahdatabases. By the end of 2015, they include 11182 articles. The studyaims to present quantitive and qualitative analysis of research trends inthese journals, using the bibliometric method. The results indicate that, thepublication of these journals is limited to eight countries, namely: Egypt,Saudi Arabia, Iraq, Tunisia, Jordan, Algeria, Libya, and Syria. Fifty-fourpercent of these articles are available in full text, while forty-six percent ofthem have only bibliographic data. Eighteen journals are still running, whilefifteen have been discontinued from publication. Only seven journals areupdated until 2015 in the databases